An Update on Pineapple Leaf Fibers - Shiyu Liao; Jianming Chen; Xungai Wang (Journal of Natural Fibers)
Pineapple Leaf Fiber (PALF), usually recognized as a sustainable material, is derived from agricultural waste with versatilities and great values for textile and composite applications. This review provides a comprehensive summary and update on PALF, tracing its journey from plantation to final product by offering an explicit introduction of its production, properties, processing, and applications. It begins with an outline on the PALF’s cultivation, distribution, and production. Then, the complex processing of PALF is well demonstrated by investigating the technological advancements across three decades in extraction methods and degumming techniques, including biological, and synergistic approaches. Subsequently, the structure and properties of PALF are discussed in terms of anatomical structure, chemical composition, mechanical strength, thermal behavior, and antimicrobial properties. In addition, the effects of different chemical modifications on PALF’s properties are summarized, highlighting the fiber’s remarkable versatility. This study further maps PALF’s diverse applications along with the corresponding processing techniques. These applications span from textile manufacturing, composite materials to innovative waste utilization strategies. From knitted fabrics, aerogels to creative waste management solutions like fuel briquettes, it underscores the fiber’s transformative potential. Supported by a rigorous Life Cycle Assessment (LCA), this review evaluates PALF’s environmental impact, positioning it as a revolutionary sustainable material that aligns with circular economic principles.